Human personality privacy analysis based on visual features - Jie NIE; Lei HUANG; Zhen LI; Jian ZHANG; Yan YAN; Zhi-qiang WEI (Tongxin xuebao)
Personalized recommendation in social media attempts to analyze the habits and personality based on the loca-tion information and pictures from the users' comments on the public platform. This is very useful for personalized in-formation recommendation. But from perspective of privacy protection, this will affect the privacy security. A novel hu-man personality privacy analysis method based on portrait was proposed. By analyzing the personality model of the psy-chology, five visual features were proposed, including color features, texture features, shape features, Itten contrast fea-tures and expression features. Comprehensive experiments demonstrate the effectiveness of the proposed method. Further, the features analysis experiment show that the proposed features are very relevant to human personality privacy analyz-ing.